2012
DOI: 10.1080/21568316.2012.726256
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Networking in an Emerging Ecotourism Destination

Abstract: This paper presents the results of a study of planned ecotourism destination development in an economically marginal rural area on the border between Ireland and Northern Ireland. The initiative, which was funded primarily from European Union sources, was administered by a network consisting of representatives of local authorities, national tourism bodies, regional and rural development groups, and ecotourism providers. The paper focuses on the organizational network and its networking in promoting ecotourism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…They also suggested that the unique and natural, but remote and peripheral environment of Connemara favoured the tourist industry, which has become a sustaining influence in the region. Similar studies by Che (2006) and Conway and Cawley (2012) suggest that peripheral regions of high ecotourist value are increasingly favoured by the industry. Similarly, McDonagh (2002a) suggests that peripheral places where authentic isolation and remoteness has been transformed into a tourist attraction strategy are increasingly favoured as tourist destinations.…”
Section: Category 1: Understanding the Phenomenon Of Marginality And supporting
confidence: 68%
“…They also suggested that the unique and natural, but remote and peripheral environment of Connemara favoured the tourist industry, which has become a sustaining influence in the region. Similar studies by Che (2006) and Conway and Cawley (2012) suggest that peripheral regions of high ecotourist value are increasingly favoured by the industry. Similarly, McDonagh (2002a) suggests that peripheral places where authentic isolation and remoteness has been transformed into a tourist attraction strategy are increasingly favoured as tourist destinations.…”
Section: Category 1: Understanding the Phenomenon Of Marginality And supporting
confidence: 68%
“…An important consideration is also the nature of the relationships within a community or local place and the fact that these linkages can be 'soft' or 'hard' ( Saxena et al, 2007) , formal or informal ( Petrou et al, 2007) (), weak or strong (Granovetter, 1973) and often rely on the social norms and personal connections of individuals (Saxena, 2007) and as Petrou et al (2007, p.436) state 'whether to network is as much as social as an economic decision. The important role institutions can have in these networks is also observed by Cawley et al (2007) and Conway and Cawley (2012). , Kylanen and Mariani (2012) highlight the importance of coopetition, the simultaneous cooperation and competition in tourism businesses and discuss examples where 'businesses tend to cooperate in the medium-long term in order to achieve a successful long-term destination branding strategy while they compete on a shorter term for the hearts, minds and wallets of the customers ' (p.62).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The preponderance of successful cases is somewhat misleading in tourism studies since it is the more common but less studied development failures which are a better reflection of reality. Moreover, there are also minor, incremental successes through, for example, projectbased temporary networks which leave behind an almost unnoticed legacy of increased knowledge and local understanding (Brouder, 2012;Conway & Cawley, 2012). How exactly regional branching comes about is an underdeveloped research area and requires greater attention from tourism scholars.…”
Section: Path Dependence and New Path Creationmentioning
confidence: 99%